Global childhood obesity prevention policies: A systematic review and implications for Indonesia - Sari, Ayu Wulan; Flora, Rostika; Rahmiwati, Anita (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Childhood obesity is a global health problem that affects physical and mental development. Various policies have been implemented to reduce obesity rates, but their effectiveness varies across countries. To review childhood obesity prevention policies that have been implemented in various countries and identify policies that can be adapted for Indonesia. Method: This study used a systematic review method of various policy briefs that discuss the prevention of childhood obesity in the last 10 years. A search was conducted in the ubMed database, Google Scholar and DOAJ using the keywords (Obesity AND Prevention AND child OR children AND